Deformation feature and properties of Zr based bulk metallic glass treated by laser shock peening. (July 2014) - Xu, G. Y.; Wei, Y. P.; Wei, B. C.
<x content-type="archive" xml:space="preserve">Abstract</x> Laser shock peening is promising surface treatment technique to improve the mechanical properties of metals material through introducing a deep compressive residual stresses region. In this work, LSP was employed to treat Zr based bulk metallic glasses (BMGs). In contrast to the work softening in BMGs, laser shock peened BMG shows significant hardening in the plastic deformed region. Furthermore, the plastic deformation region exhibits unique deformation features, which is dependent on the thickness of the samples. The deformation morphology under the impacted region was also studied. The mechanism for the hardening and formation of unique deformation features is discussed.